EFEKTIVITAS KEBIJAKAN PENGGUNAAN LAMPU LALU LINTAS DALAM MENGATASI KEMACETAN DI KOTA CIMAHI - Vika Maulinda; Syifa Salsabilah; Zanindra Primahmudika (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
The number of vehicles continues to increase in line with economic growth, while on the other hand the growth of traffic infrastructure is not as high as the growth in the number of vehicles and community mobility. The existence of traffic lights that do not work is one of the causes of congestion at several Cimahi intersection points, it is very unfortunate when public facilities do not function optimally and are used by certain people who want to take advantage. The author in this study used a qualitative approach with a case study method. This qualitative approach was chosen by the researcher because by using a qualitative approach with the case study method, the researcher could describe in more depth the study of the effectiveness of the traffic light policy that actually happened in the field. The purpose of this study was to analyze the effectiveness of the use of traffic lights that did not work at several points in Cimahi City. The results of this study indicate that the policy regarding the use of traffic lights in Cimahi City is quite appropriate considering the use of traffic lights is vital for the regularity of traffic flow in Cimahi City, but unfortunately there are several points where traffic lights do not function to make traffic flow. uncontrollable and experiencing traffic jams because there is no budget to repair the dead traffic lights. Keywords: Effectiveness, Traffic, Community Mobility